(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2017)
This paper examines the case-study of the edition of Amelia Rosselli’s complete works, published in 2012 and edited by Stefano Giovannuzzi. The editor had to ponder over the selection and the chronology of published books, and he also had to deal with the ambiguous statements of Amelia Rosselli’s poems dating. Moreover, the previous edition of Rosselli’s work, published in 1997, can’t be considered a scientific point of reference, because it did not use any philological method and did not follow the author’s will.